(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
A balance sheet is a financial accounting overview of an individual’s or organisation ’s financial balances, whether it’s a sole proprietor, commercial partnership, corporation, commercial limited corporation, or another entity such as the governments or a not-for-profit. A receivables, obligations, and ownership equity are stated as of a certain date, such as the fiscal year’s end. A "picture of a corporation’s financial status" is how a balancing sheet is commonly referred to. The balancing sheets is the only ones of the four basic financial statements that refers to a specific moment in time throughout a company’s fiscal year. In this review article, we look at the overview of a balance sheet, the components of a balance sheet, as well as the benefits and drawbacks of a balance sheet. The future scope of the balance sheet is that Stakeholders will be able to review the balance sheet to understand the company’s liquidity status and business performance.